2017
DOI: 10.1177/1045389x17692047
|View full text |Cite
|
Sign up to set email alerts
|

State observation–based control algorithm for dynamic vibration absorbing systems featuring magnetorheological elastomers: Principle and analysis

Abstract: Based on state observation, a rapid, stable, and effective control algorithm for magnetorheological elastomer (MRE)–based dynamic vibration absorbers (DVAs) applied to automobile powertrain mount systems is proposed and investigated in this article. The state-space model for powertrain mount systems with MRE-based DVAs is established using the rank criterion method for observable systems. According to the principle of system reconfiguration, a full state observation model using an adaptive Kalman filter with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Hoang (2011) and Hoang et al (2009) designed a semi-active MRE torsional vibration absorber for the vehicle power train, and the frequency shift characteristics us-ing the hammer test were evaluated. Xin et al (2017) and Qian et al (2017) designed a vertical direction MRE vibration absorber for the vehicle mounting system, yet he studied its vibration-absorption performance; moreover, its control strategy was perfected. Rao et al (2014) designed a shearmode MRE dynamic vibration absorber to reduce the longitudinal vibration of the power-train system.…”
Section: P Gao Et Al: a New Mre Torsional Vibration Absorber: Desigmentioning
confidence: 99%
“…Hoang (2011) and Hoang et al (2009) designed a semi-active MRE torsional vibration absorber for the vehicle power train, and the frequency shift characteristics us-ing the hammer test were evaluated. Xin et al (2017) and Qian et al (2017) designed a vertical direction MRE vibration absorber for the vehicle mounting system, yet he studied its vibration-absorption performance; moreover, its control strategy was perfected. Rao et al (2014) designed a shearmode MRE dynamic vibration absorber to reduce the longitudinal vibration of the power-train system.…”
Section: P Gao Et Al: a New Mre Torsional Vibration Absorber: Desigmentioning
confidence: 99%
“…The MREs are, thus, considered to offer meritorious potentials for many engineering applications, particularly for vibration and noise reduction; thanks to their wide variations in stiffness and energy absorption properties, apart from the low response time, stability, compatibility with mechanical components and reasonably low power requirement (Li et al, 2014; Vatandoost et al, 2019). A number of studies have also demonstrated macroscopic applications of MREs such as vibration isolator for highway bridges (Yarra et al, 2018), vehicle seat suspensions (Du et al, 2011), powertrain mounts (Xin et al, 2016b), adaptive tuned vibration absorbers (ATVAs) (Qian et al, 2017; Sun et al, 2017), structural seismic mitigation as well microscopic applications such as force sensors (Li et al, 2009), soft actuator (Kashima et al, 2012), sealing eye retina detachments (Alekhina et al, 2018), MRE-based stiffness display (Hooshiar et al, 2020), and artificial lymphatic vessels (Behrooz, 2015). Besides, many semi-active MRE-based vibration suppression devices have been designed for applications in structural seismic mitigation (Gu et al, 2016, 2017, 2019; Yu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The ''bi-directional mode'' concept, in detail, assuming that one single mode vibration isolation system can only provide one mode isolation with one magnetic field actuation unit while the ''bi-directional mode'' technique offers integrating two vibration isolation systems that are independent with each other as well as realizing the two single mode vibration isolations that originally need combinations of two magnetic field systems with only one magnetic field actuation system. This concept, ''functional integration,'' has also been employed in semi-active integrated MR fluid-based seat suspension system (Bai et al, 2017). There are at least three particular advantages of the new proposed integrated vibration isolation system based on the ''bidirectional shear mode'' concept listed as follows: (1) only one mathematical model along with one coil current command for delivering magnetic field is enough to magnetically actuate two MREs that operates in shear mode at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…The viscoelastic properties of MREs, namely, the storage and loss moduli, can be controlled in a rapid, continuous, and reversible manner by applying an external magnetic field (Ginder et al, 1999; Woods et al, 2007). MREs are used in various applications such as adaptive tuned vibration absorber (Qian et al, 2017), smart material–based isolators (Li et al, 2013), vehicle seat suspension (Du et al, 2011), microcantilevers (Lee et al, 2014), microvibrations (Ying et al, 2013), sensors (Wang et al, 2009), touch-screen displays (Chen et al, 2019), magnetometers (Du and Chen 2012), prosthetic devices (Jonsdottir et al, 2015), noise barrier systems (Farshad and Le Roux 2004), sandwich beams (Zhou and Wang, 2005), negative changing stiffness isolators (Sun et al, 2015), bumper of a vehicle (Bogdanov et al, 2009), and particularly in shifting the fundamental frequency of controlled devices.…”
Section: Introductionmentioning
confidence: 99%